Hourglass - Gray, Claudia (Gray, Claudia. Evernight (Series), 2010)
After escaping from Evernight Academy, the vampire boarding school where they met, Bianca and Lucas take refuge with Black Cross, a fanatical group of vampire hunters. Bianca must hide her supernatural heritage or risk certain death at its hands. But when Black Cross captures her friend -- the vampire Balthazar -- hiding is no longer an option. Soon Bianca and Lucas are on the run again, pursued not only by Black Cross, but by the powerful leaders of Evernight. Yet no matter how far they travel, Bianca can't escape her destiny. Bianca has always believed their love could survive anything ... but can it survive what's to come?